Virtual Museum of Tsunami Project for Increasing Awareness of Disaster Risk Potential in Physics Class - Wanda Devianti; Mita Anggaryani (Universitas Lambung Mangkurat, 2022)
Virtual Reality (VR) development is expected to answer the problem of learning loss in education, especially in disaster mitigation studies. Using VR with artificial environments of scenes and objects appearing to be real, various disaster scenarios were made possible to learn. When this computer-enhanced learning was introduced to high school students, it could reduce both limitations and challenges of real-world learning. Visena (Virtual Museum of Tsunami) is virtual reality-based learning media in the form of a virtual museum which helps students understand the concept of waves and increase awareness of disaster risk potential in earthquakes and tsunamis. This study aims to test the validity, effectiveness, and practicality of Visena when it is implemented in a classroom setting. Visena was developed during the study using a 4D model of define, design, develop, and disseminate. Visena learning media were classified as very valid according to the validation process results. Student’s response were categorized very good despite a limited trial of Visena in class. Some students showed good performance with significant results when using Visena. It is recommended to use a smartphone to reduce dizziness when using glasses, and the material should be adjusted to the characteristics of the students. Therefore, an introduction to learning material and teacher assistance is needed.